Risk factors in the South African banking industry: the role of capital, bank size, leverage and franchise value - Khan, Nkwenti Chalie (My University, 2016)
The recent failure rate of financial institutions and banks has put risk management at the center of regulatory authority’s attention, not leaving out the banking sector. This study empirically investigates the relationship between several risk factors including the capital-to-assets ratio (CAR), franchise value, bank size and operating leverage; and bank risk in the South African banking sector before, during and after the financial crises covering the period 2004 - 2015. A cross-sectional approach is employed on daily price data from publicly listed South African bank holding companies to model risk in the sector and present potential red flags to regulators and policy makers. Findings provide evidence of a negative relationship between the CAR and bank risk in non-crises years and a positive relationship during the crises while a non-linear relationship between franchise value and bank risk is confirmed. No such study has been conducted yet in the South African context, while very few have been done within an African country context. Even at that, the only study to have combined several risk factors to study effects of bank risk is that by Gregory and Hambusch, (2015) on the US banking sector.
Master of Management in Finance and Investment Wits Business School University of the Witwatersrand 2016